Successful Management of Gastrointestinal Haemorrhage Associated with Ischaemic Colonic Ulceration in Acute Pancreatitis with Video Assisted Retroperitoneal Debridement - Puri, Yogesh; Rahman, Sakhawat H (JOP. Journal of the Pancreas, 2011)
Context Colonic involvement is an uncommon but potentially lethal complication of severe acute pancreatitis and has received little attention in the surgical literature. Such complications can range from localized colonic pathology to widespread ischaemic pancolitis. Treatment options have historically been limited to resection of the affected segment. Case report We describe the successful role of video assisted retroperitoneal pancreatic debridement in the management of two cases presenting with major gastrointestinal haemorrhage due to localised colonic ulceration on the background of acute necrotising pancreatitis. Conclusion Video assisted retroperitoneal debridement should be considered early in the management of local colonic complications associated with severe acute necrotising pancreatitis. Image: Involvement of mesocolon by pancreatic inflammatory process.